2018
DOI: 10.1016/j.psychsport.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The 2 × 2 model of perfectionism and youth sport participation: A mixed-methods approach

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 36 publications
3
23
0
1
Order By: Relevance
“…In a study of youth in the United States participating in a track program, Sirard and colleagues [31] found that girls participated in sport for mainly social benefits, but also competition and fitness, whereas boys participated mainly for competition, but also for socializing and fitness. Moreover, adolescent girls specifically expected to participate in sport in a welcoming and supportive environment [32] and to receive support from their peers, their family, and their coach [27,29]. These findings indicate that youth who exhibit different characteristics will hold different expectations for their sport and physical activity experiences.…”
Section: Youth Sport and Physical Activity Consumptionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study of youth in the United States participating in a track program, Sirard and colleagues [31] found that girls participated in sport for mainly social benefits, but also competition and fitness, whereas boys participated mainly for competition, but also for socializing and fitness. Moreover, adolescent girls specifically expected to participate in sport in a welcoming and supportive environment [32] and to receive support from their peers, their family, and their coach [27,29]. These findings indicate that youth who exhibit different characteristics will hold different expectations for their sport and physical activity experiences.…”
Section: Youth Sport and Physical Activity Consumptionmentioning
confidence: 97%
“…Consumers engage in autotelic actions for the sake of the activity [26]. Many youths consume sport and physical activity for autotelic purposes; they participate for a fun experience [12,[27][28][29][30]. For instance, when investigating factors that influence adolescent girls' sport and physical activity behaviours in Australia, Casey and colleagues [27] found that fun activities and being with friends were two of the strongest reasons for participation in sport and physical activity.…”
Section: Youth Sport and Physical Activity Consumptionmentioning
confidence: 99%
“…In terms of evaluating research rigour, some researchers addressed integrative quality criteria that they framed as applicable to the study as a whole (e.g., Karageorghis et al, 2018;Mallinson-Howard et al, 2018;Rumbold et al, 2018;Thrower et al, 2019), but more often quantitative and qualitative parts of the study were evaluated separately (e.g., Kacperski & Hall, 2017;Middleton et al, 2017;Redwood-Brown et al, 2018;Richard et al, 2017;Whitehead et al, 2018). From the integrative perspective, Thrower et al (2019) suggested that "taken as a whole, this study can be judged on the capacity to which it is relevant for the research questions, is transparent, has a rationale for using mixed methods, and requires the integration of mixed-method findings", while at the same time maintaining that "the quality criteria for each aspect of the study should be considered separately" (p. 4).…”
Section: Considerations Of Research Qualitymentioning
confidence: 99%
“…Sport is conceived as a personal space. It could be explained, based on [ 30 ], a mixed-methods study, which revealed that the meaning youth sport participants gave to their sport involvement (i.e., goals, values, and purposes) and the features of the social-environment they perceived to be important differed between the four subtypes of perfectionism. Researchers concluded that youth sport participants demonstrate different subtypes of perfectionism and vary in their experiences of youth sport.…”
Section: Discussionmentioning
confidence: 99%